Optical properties of β-FeSi2 Thin films grown by magnetron sputtering - Tatar, B.; Kutlu, K. (AMER INST PHYSICS, 2007)
beta-FeSi2 semiconductor thin films have been grown on Si(100) and Si(111) substrate at room temperature by unbalanced magnetron sputtering. The thicknesses of beta-FeSi2 thin films have been prepared to have value between 0.3-1 mu m. Optical characteristic of the beta-FeSi2 films have been deduced using Fourier Transform Infrared Spectroscopy (FT-IR) in the wavelength range 1000-2000nm. The beta-FeSi2 films have been determinated to have optical direct band gap from the plot of (alpha h upsilon)(2) vs. h upsilon. The direct band gap values of the films have been observed to vary between 0.82-0.89 eV depending on the type of substrates.
Keywords: silicide; optical band gap; absorbsiyon; beta-FeSi2 films; FT-IR; Physics